2020
DOI: 10.1177/1758835920953292
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of anemia in cancer patients undergoing chemotherapy with intravenous ferric carboxymaltose without erythropoiesis-stimulating agents

Abstract: Background: Anemia is commonly encountered in cancer patients receiving active chemotherapy. Due to adverse events and presumed negative effects on disease-progression and survival, erythropoiesis-stimulating agents are not frequently used. In this study, we assess the efficacy and safety of intravenous ferric carboxymaltose (FCM) to treat cancer-induced anemia (CIA). Patients and Methods: We recruited adult cancer patients on active chemotherapy with a hemoglobin (Hb) level ⩽11.0 g/dL. Based on serum ferritin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…The overall treatment response rate was 59.5%, while a difference was noted between the absolute and functional iron deficiency groups (80.8% vs. 70.8%). Although the results of the study indicate that the effectiveness may be lower in patients with functional iron-deficiency anemia, treatment success is still high in both groups and consistent with our findings [24].…”
Section: Discussionsupporting
confidence: 90%
“…The overall treatment response rate was 59.5%, while a difference was noted between the absolute and functional iron deficiency groups (80.8% vs. 70.8%). Although the results of the study indicate that the effectiveness may be lower in patients with functional iron-deficiency anemia, treatment success is still high in both groups and consistent with our findings [24].…”
Section: Discussionsupporting
confidence: 90%
“… 17 , 18 , 29 However, recent several studies have assessed the efficacy of IV iron as a monotherapy for CIA; these studies have consistently demonstrated increases in Hb levels and/or notable reductions in transfusion rates. 19 , 20 , 30 33 One example is the IRON-CLAD study, which showed that IV iron supplementation, specifically in the form of FCM monotherapy, allowed most patients receiving chemotherapy to maintain Hb levels within 0.5 g/dL of baseline, and was significantly more effective in doing so when compared with a placebo. 30 The PROFOUND trial, demonstrated that iron isomaltoside and oral iron produced comparable sustained increases in Hb concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have defined it as a Hb increase of ⩾2.0 g/dL or Hb of ⩾12.0 g/dL, 17 , 18 whereas recent studies have defined it as a Hb increase of ⩾1.0 g/dL or Hb of ⩾11.0 g/dL. 19 , 20 In the present study, Hb response was defined as a Hb increase of ⩾1.0 g/dL or a Hb of ⩾11.0 g/dL within 3 months following CIA treatment without an RBC transfusion. The proportion of patients receiving a PRC transfusion within 6 months of the baseline and the time to PRC transfusion were also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The same meta-analysis also reported the efficacy of IV iron alone, while only a few smaller trials were available at that time (44). Indeed, with the recent advent of modern third-generation IV iron preparations (45), evidence is accumulating on the efficacy of iron monotherapy in CCRA (46)(47)(48)(49). CCRA patients with concomitant AID are the most suitable candidates for this approach, but diagnosing AID in cancer patients using traditional iron biomarkers is challenging (6), due, for example, to ferritin upregulation by tumor necrosis factor-alpha (TNF-a) and pro-inflammatory cytokines (50,51).…”
Section: Iron Supplementationmentioning
confidence: 99%